The Actin Binding Protein, Fesselin, is a Member of the Synaptopodin Family - Schroeter, Mechthild M.; Beall, Brent; Heid, Hans W.; Chalovich, Joseph (East Carolina University, 2008)
Fesselin is a natively unfolded protein that is abundant in avian smooth muscle. Like many natively unfolded proteins, fesselin has multiple binding partners including actin, myosin, calmodulin and Î±-actinin. Fesselin accelerates actin polymerization and bundles actin. These and other observations suggest that fesselin is a component of the cytoskeleton. We have now cloned fesselin and have determined the cDNA derived amino acid sequence. We verified parts of the sequence by Edman analysis and by mass spectroscopy. Our results confirmed fesselin is homologous to human synaptopodin 2 and belongs to the synaptopodin family of proteins. Originally published Biochem Biophys Res Commun. Vol. 371, No. 3, July 2008
Keywords: Fesselin; Synaptopodin; Myopodin; Actin binding protein; Actin polymerization; Ca-calmodulin regulation